Analysis of Mathematical Reasoning Abilities Based on PISA Number Content - Cici Imelda Sabri. L; Salim (Jurnal Amal Pendidikan, 2024)
This study aims to determine the mathematical reasoning abilities of eighth-grade students at SMP Negeri 1 Kulisusu Utara in solving PISA-based mathematics problems in the content of numbers. This research is a qualitative descriptive study. The subjects of this study were 3 students from class VIIIB at SMP Negeri 1 Kulisusu Utara, conducted during the 2020/2021 academic year. Data collection techniques included tests, interviews, and documentation. The data analysis technique used was descriptive analysis, employing the theory of Miles, Huberman, and Saldana, which involves data condensation, data presentation, and drawing conclusions. The results of the study indicated that: Students with high mathematical abilities in solving PISA number content problems were found to have high mathematical reasoning abilities. Students with moderate mathematical abilities in solving PISA number content problems were found to have moderate mathematical reasoning abilities. Students with low mathematical abilities in solving PISA number content problems were found to have moderate mathematical reasoning abilities.